2019
DOI: 10.21323/2414-438x-2019-4-1-21-29
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Atmospheric-Pressure Plasma in Microbial Decontamination and Meat Technology. A Review

Abstract: The development of plasma technology is associated with the unique features of non-equilibrium low-temperature plasma: high electron energy and high concentration of chemically active excited and charged particles at low gas temperature, which allows to process thermolabile materials and biological objects in gentle conditions when high temperatures are not required. The biological effects of low-temperature plasma exposure are considered. It was established that during plasma treatment, a combined effect on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Treatment of suspension cells was described in Gabriel et al (2016) , where a 5 log decrease was observed after 25 min of exposure. The efficiency of decontamination of agar plates was studied in several papers ( Justan et al, 2014 ; Metelmann et al, 2018 ; Gorbunova, 2019 ; Lee et al, 2019 ), where inhibition zones were observed from several seconds to 10 min of exposure depending on the NTP source and arrangement. In addition, a more than 3 log decrease of viable cells on inoculated steel plates was observed after 20 min NTP exposure in the study by Lis et al (2018) .…”
Section: Non-thermal Plasma Treatment Of Eskape Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of suspension cells was described in Gabriel et al (2016) , where a 5 log decrease was observed after 25 min of exposure. The efficiency of decontamination of agar plates was studied in several papers ( Justan et al, 2014 ; Metelmann et al, 2018 ; Gorbunova, 2019 ; Lee et al, 2019 ), where inhibition zones were observed from several seconds to 10 min of exposure depending on the NTP source and arrangement. In addition, a more than 3 log decrease of viable cells on inoculated steel plates was observed after 20 min NTP exposure in the study by Lis et al (2018) .…”
Section: Non-thermal Plasma Treatment Of Eskape Pathogensmentioning
confidence: 99%
“… Gorbunova (2019) described the possibilities of using NTP in the food industry for processing and preserving meat products. A collection of bacterial strains was exposed in model experiments, where K. pneumoniae was inhibited after a 10-min exposure by 36%.…”
Section: Non-thermal Plasma Treatment Of Eskape Pathogensmentioning
confidence: 99%
“…Cold atmospheric pressure plasma (CAP) has found novel applications in medicine, food processing, material processing and microelectronics industries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%